1985
DOI: 10.1104/pp.79.3.920
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activation of Phosphoglucomutase by Fructose 2,6-Bisphosphate

Abstract: The hexose bisphosphate activation of phosphoglucomutase was investipted with both plant (pea and mung bean) and animal (rabbit muscle) sources of the enzyme. Plant phosphoglucomutase was purified about 50-fold from seeds, and to a lesser extent, from seedlings of Pisum sativum L. cv Grenadier and seedlings of Phaseolus aureus. It was found that the plant enzyme was isolated in a mostly dephosphorylated form while commercial rabbit muscle phosphoglucomutase was predominantly in the phosphorylated form. Activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 2 publications
3
11
1
Order By: Relevance
“…Conflicting results have been reported as to the effect of Fru 2,6-P2 on the enzyme PGM. While some investigators have reported an inhibition of PGM by Fru 2,6-P2 (1, 4), we have reported a stimulation (7). PGM, the enzyme responsible for the interconversion of Glc 1-P and Glc 6-P, occupies a central position in the pathway of sugar metabolism.…”
contrasting
confidence: 54%
“…Conflicting results have been reported as to the effect of Fru 2,6-P2 on the enzyme PGM. While some investigators have reported an inhibition of PGM by Fru 2,6-P2 (1, 4), we have reported a stimulation (7). PGM, the enzyme responsible for the interconversion of Glc 1-P and Glc 6-P, occupies a central position in the pathway of sugar metabolism.…”
contrasting
confidence: 54%
“…However, it has been recently reported that phosphoglucomutase from pea and mung bean, in the absence of glu-1,6-P2, is activated by fru-2,6-P2 (5 MATERIALS AND METHODS Chemicals. Glucose 1-P, glucose 6-P, glu-1 ,6-P2, fructose 6-P, fructose 1,6-P2, glycerate 3-P, glycerate 2,3-P2, NADP, ATP, glucose 6-P dehydrogenase from yeast, and phosphoglucomutase from rabbit muscle were obtained from Boehringer.…”
mentioning
confidence: 99%
“…Authentic glucose-1,6-bisP was obtained from Sigma. Reaction mixture conditions for soybean leaf PGM were established experimentally in this laboratory using modifications of previously decribed procedures (9,19,29). Preparations of freshly extracted PGM from animal tissues do not require glucose-1,6-bisP as a cofactor, as long as the enzyme remains phosphorylated (9).…”
Section: Leaf Enzyme Assaysmentioning
confidence: 99%
“…Reaction mixture conditions for soybean leaf PGM were established experimentally in this laboratory using modifications of previously decribed procedures (9,19,29). Preparations of freshly extracted PGM from animal tissues do not require glucose-1,6-bisP as a cofactor, as long as the enzyme remains phosphorylated (9). In contrast, green plant PGM is not phosphorylated in vivo, and requires glucose-1,6-bisP as an obligate cofactor (9,29).…”
Section: Leaf Enzyme Assaysmentioning
confidence: 99%
See 1 more Smart Citation